Exploring the Nexus and Utilities Between Regional and Global Ocean Governance Architecture - Adewumi, Ibukun Jacob (Frontiers in Marine Science, 2021)
Regional and global ocean governance share complex, co-evolutionary histories in which both regimes – among others – interacted with and used the ocean and resources therein to consolidate, expand, and express power. Simultaneously, regional and global ocean governance relations have changed continuously, particularly when we are trying to understand their differences within the logic of regionalisation, regionalism, and globalisation. The paper is generally based on deductive reasoning and reflects scholarship in security studies, political science, international law, international relation, development studies, and African studies. It delves into the critical aspect of understanding the nexus/relationship between regional and global ocean governance in critical traditional and contemporary ocean policy domains, specifically from an African regional ocean governance standpoint. Ocean governance processes that are historically confronted by globalisation, multilateralism, and post-colonisation are confronted by the rise of regionalism, especially the need for nation-states and regions to respond to and manage traditional and emerging ocean challenges. Responses to these challenges by various actors, including states, economic blocks, private sector, financial institutions, and non-governmental organisations, development partners, etc., result in different forms of relationships that refocus regions’ activities toward globally defined ocean agendas. A review of different policy domains (including maritime security, environmental, economic, and socio-political governance) critical for regional ocean governance sets a robust background for understanding the contextual factors and concerns inherent in the regional-global ocean governance nexus. These outcomes, therefore, help us to arrive at a five-fold taxonomy of different types/degrees of linkages developed around the regional-global ocean governance relationship spectrum described as (1) discrete, (2) conflictual, (3) cooperative, (4) symmetric, and (5) ambiguous. Comparatively, experience and perspective from Africa are utilised to support raised arguments about these linkages. Furthermore, this spectrum allows for the diagnosis of the utilities and most prevalent arguments that regional governance’s effectiveness is directly related to the nature of the interaction between regional governance schemes and global governance; and vice-versa. This paper’s outcomes reveal how government, institutions, actors, and researchers address the relationship between regional and global ocean governance and generate a valuable way to think about current and future global and regional ocean governance direction while outlining some logical possibilities for an effective form of ocean governance.